2022
DOI: 10.3390/curroncol29080455
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Oncology Trial Design and Uncertainties in Efficacy-Safety Data on Health Technology Assessments

Abstract: Background: Advances in cancer medicines have resulted in tangible health impacts, but the magnitude of benefits of approved cancer medicines could vary greatly. Health Technology Assessment (HTA) is a multidisciplinary process used to inform resource allocation through a systematic value assessment of health technology. This paper reviews the challenges in conducting HTA for cancer medicines arising from oncology trial designs and uncertainties of safety-efficacy data. Methods: Multiple databases (PubMed, Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 112 publications
(139 reference statements)
0
14
0
Order By: Relevance
“…Ideally RWE should primarily be used to inform policymaking, through analysis of patterns of health service utilization and identification of structural barriers to access to care, and to help shape strategies for patient-centric coverage and reimbursement decisions, including in the context of health technology assessments. 19,20 In conclusion, the SEER-analysis by Goyal et al 2 presents confirmatory RWE for the benefit of CDK4/6 inhibitors observed in clinical trials for endocrine sensitive, de novo, metastatic BC in an older population. However, this evidence is not a substitute for the results from phase 3, randomized clinical trials.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Ideally RWE should primarily be used to inform policymaking, through analysis of patterns of health service utilization and identification of structural barriers to access to care, and to help shape strategies for patient-centric coverage and reimbursement decisions, including in the context of health technology assessments. 19,20 In conclusion, the SEER-analysis by Goyal et al 2 presents confirmatory RWE for the benefit of CDK4/6 inhibitors observed in clinical trials for endocrine sensitive, de novo, metastatic BC in an older population. However, this evidence is not a substitute for the results from phase 3, randomized clinical trials.…”
mentioning
confidence: 81%
“…Randomization intrinsically minimizes bias in patient selection, ensuring fair comparisons across balanced groups. Ideally RWE should primarily be used to inform policymaking, through analysis of patterns of health service utilization and identification of structural barriers to access to care, and to help shape strategies for patient‐centric coverage and reimbursement decisions, including in the context of health technology assessments 19,20 …”
mentioning
confidence: 99%
“…Such mandatory reassessment, particularly for drugs originally approved on the basis of potentially unreliable surrogate measures, could also be an opportunity to require follow-up clinical studies conducted while a drug is in routine use. This kind of ongoing evaluation is far more useful for clinicians, patients, and policy makers than a simplistic approval decision made at a single, early point in time on the basis of potentially inadequate outcome measures but not informed by further evidence . Experience in the US indicates that manufacturers are often slow or even inert in implementing such postmarketing requirements required by the Food and Drug Administration, but the concept of reexamination does open the door to such a more systematic assessment after a drug has been approved quickly on the basis of less dependable measures.…”
mentioning
confidence: 99%
“…This kind of ongoing evaluation is far more useful for clinicians, patients, and policy makers than a simplistic approval decision made at a single, early point in time on the basis of potentially inadequate outcome measures but not informed by further evidence. 7 Experience in the US indicates that manufacturers are often slow or even inert in implementing such postmarketing requirements required by the Food and Drug Administration, 8,9…”
mentioning
confidence: 99%
“…This is important because traditional endpoints in interventional cancer trials, such as progression-free survival (PFS) or overall survival, do not correlate well with QoL (8). Surrogate endpoints have created uncertainties in translating surrogate measures into patient-centric clinically and economically meaningful outcomes (9). Nevertheless, in the last decade, such surrogate markers like PFS and tumour response have been increasingly used in clinical trials to reduce trial cost by…”
mentioning
confidence: 99%